Relation between adenomyosis and elastographic characteristics of the cervix. Issue 4 (3rd March 2023) - Xholli, A; Molinari, F; Oppedisano, F; Scovazzi, U; Vacca, I; Schiaffino, M G; Cavalli, E; Cagnacci, A
Abstract: STUDY QUESTION: Is there a possible etiologic link between cervical stiffness and adenomyosis? SUMMARY ANSWER: Women with adenomyosis have a stiffer internal cervical os than those without adenomyosis. WHAT IS KNOWN ALREADY: An increased myometrial contractility during menses, leading to breaches in the endometrial basal lamina and subsequent infiltration of endometrial cells into the myometrium, has been proposed as a possible pathogenic mechanism for adenomyosis. Intense menstrual pain has already been shown to be associated with an increased stiffness, at elastography, of the internal cervical os. STUDY DESIGN, SIZE, DURATION: A cross-sectional study on 275 women was performed between 1 February and 31 July 2022. PARTICIPANTS/MATERIALS, SETTING, METHODS: Among the participants, 103 were and 172 women were not affected by adenomyosis as evaluated by ultrasonography. General and clinical characteristics of the patients were collected. Strain elastography was used to document tissue stiffness at different regions of interest of the cervix, i.e. the internal cervical os, the middle cervical canal, the anterior and the posterior cervical compartment. Tissue stiffness was expressed as a colour score from 0.1 = blue/violet (high stiffness) to 3.0 = red (low stiffness). Simple and multiple logistic regression analyses were used to evaluate the relation between the presence of adenomyosis, as the dependent variable, and independent factors. MAIN RESULTS AND THE ROLE OF CHANCE: Women with adenomyosis had a higher prevalence ( P = 0.0001) and intensity ( P = 0.0001) of pain during menses, between menses and at intercourse compared to control. The internal cervical os colour score was lower (higher stiffness) in women with adenomyosis (0.55 ± 0.29 versus 0.67 ± 0.26; P = 0.001) and the middle cervical canal/internal cervical os colour score ratio was greater (3.32 ± 4.36 versus 2.59 ± 4.99; P = 0.008), compared to controls. Upon logistic regression modelling ( R 2 = 0.077), the internal cervical os stiffness was an independent factor related to adenomyosis (odds ratio (OR) 0.220, 95% CI 0.077, 0.627; P = 0.005) along with age ( P = 0.005) and the use of gonadal steroid therapies ( P = 0.002). We obtained the same results using a different logistic regression model ( R 2 = 0.069), by substituting the internal cervical os stiffness with the ratio of the middle cervical canal/internal cervical os stiffness (OR 1.157, 95% CI 1.024, 1.309; P = 0.019). LIMITATIONS, REASONS FOR CAUTION: Women did not undergo surgery therefore we have no histological confirmation of the adenomyosis diagnosis. Strain elastography is a semiquantitative analysis and can be conditioned by the force applied by the operator during the analysis. The data were obtained mainly in White women in a single centre. WIDER IMPLICATIONS OF THE FINDINGS: To the best of our knowledge, this is the first study indicating that women with adenomyosis have an increased stiffness of the internal cervical os. The results indicate that a stiff internal cervical os, as determined by elastography, is a possible contributor to the development of adenomyosis. These findings may have clinical significance and should prompt further investigation. STUDY FUNDING/COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: N/A.